Large-pore silica spheres as support for samarium-coordinated undecamolybdophosphate: Oxidative desulfurization of diesels - Mirante, Fátima (2020)
A novel composite has been prepared through the immobilization of the Keggin sandwich-type [Sm (PMo11O39)(2)](11-) anion (SmPOM) on large-pore silica spheres previously functionalized with trimethylammonium groups (TMA). The resulting SmPOM@TMA-LPMS material has been evaluated as heterogeneous catalyst in a biphasic desulfurization 1:1 diesel/extraction solvent system using H2O2 as oxidant. Preliminary experiments were conducted with different extraction solvents, acetonitrile and [BMIM]PF6 ionic liquid. The optimized extractive and catalytic oxidative desulfurization system (ECODS) with [BMIM]PF6 was able to reach complete sulfur removal from a model diesel containing 2100 ppm S in just 60 min (10 min of initial extraction + 50 min of catalytic step). The reutilization of catalyst and extraction phase has been successfully performed without loss of desulfurization efficiency in consecutive cycles, turning the process more sustainable and cog-effective. The remarkable results with simulated diesel have motivated the application of the catalyst in the desulfurization of untreated real diesel and 74% of efficiency was achieved after only 2 h for three consecutive cycles.